Measuring and Assessing the State of Technological Innovations and the Level of Interaction between Rice Processors and Stakeholders in Rice Processing Industry in Nigeria - Olufemi, AKINTELU Sunday (International Journal of Business, Economics and Management, 2018)
The study examined the state of technological innovations in rice processing industry and investigated the level of interaction that exists between rice processors and stakeholders involved in rice processing operations in Nigeria. Data were collected from 35 (12 integrated and 23 medium and small-scale mills) rice processing firms in four geopolitical zones of Nigeria through the use of questionnaire. These firms were selected using snow balling sampling technique. The questionnaire elicited information on the state of technological innovations in the firms and the level of existing interactions among rice processors and relevant stakeholders. Data were analyzed using descriptive statistics. The result showed that majority (71.4%) of the firms had technological innovations involving introduction and improvement of existing product and 45.7% of them had technological innovations involving introduction of a new process and improvement of the existing process. More than two thirds (82.9%) of the firms carried out technological innovations mainly by themselves. Also, 65.7% of the technological innovations originated mainly in Nigeria, 31.4% were imported while 2.9% were sourced jointly in Nigeria and abroad. The results further showed that the firms have low (mean < 2.58) level of interactions with important stakeholders such as banks, local suppliers of equipment, universities/research institutes, foreign firms and government with a mean of 2.91, 2.57, 2.49, 2.09 and 1.86 respectively. The study concluded that to enhance technological innovation in Nigerian rice processing industry, there is a need for the development of strong linkage between the industry and the stakeholders involved in rice processing operations.